2015
DOI: 10.1039/c5ee00204d
|View full text |Cite
|
Sign up to set email alerts
|

Reductive lignocellulose fractionation into soluble lignin-derived phenolic monomers and dimers and processable carbohydrate pulps

Abstract: A catalytic lignocellulose biorefinery process is presented, valorizing both polysaccharide and lignin components into a handful of chemicals. To that end, birch sawdust is efficiently delignified through simultaneous solvolysis and catalytic hydrogenolysis in the presence of a Ru on carbon catalyst (Ru/C) in methanol under a H-2 atmosphere at elevated temperature, resulting in a carbohydrate pulp and a lignin oil. The lignin oil yields above 50% of phenolic monomers (mainly 4-n-propylguaiacol and 4-n-propylsy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

35
778
1
11

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 754 publications
(850 citation statements)
references
References 123 publications
35
778
1
11
Order By: Relevance
“…To our surprise, at 180 °C, the small molecule fraction of the liquid phase contained predominantly one aromatic compound, dihydroconiferyl alcohol (1G), which could be isolated. Earlier studies using noble-metal catalysts and higher temperatures reported 2G as the main product in mixtures, and 1G was also seen before 16 . Remarkably, in our system 1G was obtained in excellent (> 90%) selectivity (Fig.…”
Section: Nature Catalysismentioning
confidence: 99%
See 2 more Smart Citations
“…To our surprise, at 180 °C, the small molecule fraction of the liquid phase contained predominantly one aromatic compound, dihydroconiferyl alcohol (1G), which could be isolated. Earlier studies using noble-metal catalysts and higher temperatures reported 2G as the main product in mixtures, and 1G was also seen before 16 . Remarkably, in our system 1G was obtained in excellent (> 90%) selectivity (Fig.…”
Section: Nature Catalysismentioning
confidence: 99%
“…While these methods hold much promise for the selective production of aromatic monomers from the lignin fraction, they leave a significant portion of the renewable carbon equivalents unutilized and mixed with the catalyst. Thus, in these systems it is (mainly) the cellulose part that is tedious to valorize and catalyst recycling has been identified as a key challenge 4,16 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…12 Effective utilization of lignin remains a major intellectual challenge [1][2][3] that is drawing increasing interest from the chemical community. [13][14][15][16][17][18][19][20] Our laboratories previously demonstrated the clean reductive disassembly of organosolv lignin to organic liquids without formation of intractable chars or tars. 21 This process is heterogeneously catalysed by a copper-doped porous metal oxide (Cu20PMO) that is prepared by calcining a 3 : 1 Mg 2+ : Al 3+ hydrotalcite in which 20% of the Mg 2+ had been replaced by Cu 2+ .…”
Section: Introductionmentioning
confidence: 99%
“…Lignin has a high economic impact, as it hinders the industrial processing of lignocellulosic biomass into pulp and fermentable sugars, leading to large economic costs to extract it from the biomass. On the other hand, lignin is increasingly considered as a potentially valuable product, and new applications and profit revenues for this biopolymer are being identified (Ragauskas et al, 2014;Van den Bosch et al, 2015). In Norway spruce (Picea abies), an economically important conifer in Europe, lignin is composed mainly of coniferyl alcohol giving rise to G units, with a small proportion of p-coumaryl alcohol-derived H units (Boerjan et al, 2003).…”
mentioning
confidence: 99%